An electronic tongue system with automatic sample mixing function for long-term in-situ monitoring of chemical reactions - Chaoxian Jia; Yuezhong Mao; Jianxi Ying; Xiaofan Guo; Shiyi Tian; Weibo Zheng; Tao Zhang; Yufen Zhao; Kun Ding; Yan Liu (Electrochemistry Communications)
As technology advanced, the demand for automation and in-situ monitoring of chemical reactions soared. This article introduced a novel in-situ monitoring device that utilized an electronic tongue system. Comprising a centrifuge, experimental unit, microfluidic chip, and electronic tongue plug (or stopper), the device facilitated simultaneous sample mixing, stimulus signaling, and response signal collection. The chip, serving as the carrier for the samples, provided a stable and sealed environment, which was crucial for electronic tongue monitoring. Acting as the plug for the chip, the electronic tongue enabled in-situ monitoring of liquids. Proven effective in studying nucleotide selection and amino acid regulation during peptide formation, this device broadened the possibilities of automated monitoring designs and was deployed in the Wentian module of Tiangong space station, advancing the application prospects of the electronic tongue system in space chemistry.